The Chromosome 9p21 CVD- and T2D-Associated Regions in a Norwegian Population (The HUNT2 Survey) - Øyvind Helgeland; Jens K. Hertel; Anders Molven; Helge Ræder; Carl G. P. Platou; Kristian Midthjell; Kristian Hveem; Ottar Nygård; Pål R. Njølstad; Stefan Johansson (International Journal of Endocrinology)
Background. Two adjacent regions upstream CDKN2B on chromosome 9p21 have been associated with type 2 diabetes (T2D) and progression of cardiovascular disease (CVD). The precise location and number of risk variants have not been completely delineated and a possible synergistic relationship between the adjacent regions is not fully addressed. By a population based cross-sectional case-control design, we genotyped 18 SNPs upstream of CDKN2B tagging 138 kb in and around two LD-blocks associated with CVD and T2D and investigated associations with T2D, angina pectoris (AP), myocardial infarction (MI), coronary heart disease (CHD; AP or AMI), and stroke using 5,564 subjects from HUNT2. Results. Single point and haplotype analysis showed evidence for only one common T2D risk haplotype (rs10757282∣rs10811661: OR = 1.19, P=2.0×10-3) in the region. We confirmed the strong association between SNPs in the 60 kb CVD region with AP, MI, and CHD (P<0.01). Conditioning on the lead SNPs in the region, we observed two suggestive independent single SNP association signals for MI, rs2065501  (P=0.03) and rs3217986  (P=0.04). Conclusions. We confirmed the association of known variants within the 9p21 interval with T2D and CHD. Our results further suggest that additional CHD susceptibility variants exist in this region.